THE ROLE OF JOB SATISFACTION MEDIATION ON THE INFLUENCE OF WORK ENVIRONMENT AND ORGANIZATIONAL SUPPORT ON EMPLOYEE PERFORMANCE - Sunardi Sunardi; Sutianingsih Sutianingsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Employee job satisfaction cannot be separated from the fact that employee job satisfaction can be achieved if all expectations can be met in carrying out their job duties. Job satisfaction is a reflection of the feelings and attitudes of individuals towards their work, which is the interaction between those concerned with their work environment. The purpose of this study is to determine the effect of the work environment, organizational support, job satisfaction, work environment, and organizational support on employee performance. This research is a quantitative study conducted on 51 employees with primary and secondary data sources obtained through questionnaires and documentation. The data obtained were analyzed using descriptive statistics and inferential statistical analysis. The results of this study are the work environment, organizational support, job satisfaction, work environment, and organizational support affect employee performance. Keywords: mediation, work, environment, support, organization